Desertion in the Bachelor Program in English Language Teaching at Uniminuto. - Moreno Saiz, William Santiago; Chaparro Robles, Daniel Eduardo (Pregrado (Presencial), 2019)
College dropout involves discussing the causes why students desert, more precisely the need to understand the reasons why they did not continue their training. Ruiz, Muriel, Gallego, Velez, Gomez & Portilla (2009) “one of the main problems that faces the Colombian higher education system, is the high level of academic desertion in the undergraduate programs” (p.13). From this point, throughout this research, we analyzed the reasons why students in the Bachelor Program in English Language Teaching at UNIMINUTO deserted. Having a population of participants between the years 2013-2017, implementing a case study research with qualitative approach using documentary evidence, survey and interviews. We expect that the results help in the permanence of the students in the program.
To analyze the reasons why learners from 2013 to 2017 of Bachelor program of English Language Teaching from UNIMINUTO desert.
Keywords: Desertion; desertor; higher education; retention; Deserción; Educación alta; Enseñanza ingles; Ingles (actitud)